Write to Learn: Investigating the Effectiveness of the 5E Model in Teaching Writing - Aryanika, Septa; Fadhila, Aulia Salsa; Puspitarini, Yulan (International Journal on Advanced Science, Education, and Religion, 2025)
This study examines the effect of the 5E instructional model (Engage, Explore, Explain, Elaborate, and Evaluate) on the writing skills in recount texts of junior high school learners. The research focuses on improving students’ ability to write recount texts in English classes, where traditional teaching methods are still commonly used. The 5E model encourages active and cooperative learning, helping students stay engaged, explore ideas, understand concepts, enhance their skills, and assess their progress. This research uses a quantitative method with an experimental design. Two classes were randomly chosen—one as the experimental group using the 5E model, and the other as the control group using traditional lectures. Students took both pre-tests and post-tests to measure their writing abilities. The data were analyzed using descriptive statistics and an independent t-test with SPSS. The findings show that students in the experimental group performed significantly better than those in the control group. The N-Gain scores also support this, with the experimental group scoring an average of 0.73 compared to 0.28 in the control group. These results suggest that the 5E instructional model effectively improves students’ writing performance, especially in junior high school.